SOCIAL-ECONOMIC ASPECTS OF COASTAL COMMUNITY THAT INFLUENCE MANGROVE FOREST DEGRADATION IN SECANGGANG VILLAGE LANGKAT REGENCY - Supriana, Tavi (Bumi Lestari; Vol 10 No 1 (2010), 2010)
The objective of this study is to analyze social-economic aspects of coastal community that influence mangrove forest degradation. Analysis is conducted for coastal community members who earn their living thru mangrove tree cutting activities. Method used is multiple linear regression analysis. The result shows that social factors (educational level, environmental knowledge level and cosmopolitan level) seem to have a significant effect on the degradation of mangrove forest. Increasing educational level and cosmopolitan level can reduce the level of mangrove deforestation. Economic factors (income and number of dependants) also have a significant role on the loss of mangrove forest. Thus, income improvement can reduce deforestation. Implications of this study are: (1) in order to reduce degree of mangrove forest degradation, the coastal community should be released from their economic dependency to mangrove forest and should be given better access to other various income sources. (2) to increase awareness of the importance of role and function of mangrove forest thru elucidation (extensive service) or visualization of the effect of degradation caused by deforestation activity which do not concern the sustainability and continuity of mangrove forest. (3) to manage regulation and monitoring system by regency government to mangrove forest product industry.